Mandatory vaccination of medical personnel against COVID-19: European standards of its introduction - I.B. Ventskivska; L.M. Deshko; O.S. Lotiuk; O.P. Vasylchenko; T.T. Narytnyk (Publishing House TRILIST, 2022)
Objective: to identify the standards of the European Court of Human Rights on the introduction of mandatory vaccination of medical personnel from COVID-19 in conditions of pandemic. The analysis has been carried out on the Decisions of the European Court of Human Rights as for vaccination matters, which formed the legal position of the Court on its implementation by the State. These decisions were divided into groups according to the conditions in which the European Council launched mandatory vaccination: the situation, which is being ordinary, one (standard vaccination against diseases well known to medical science, where vaccines have been tested and investigated thoroughly). Another one is extraordinary situation within society and state, as well as in the world, for example, COVID-19 pandemic. The standards of the European Court of Human Rights for the introduction of mandatory vaccination of medical personnel against COVID-19 in conditions of pandemic have been identified: these measures must be provided by the State legislation which is to meet quality rule of law criteria; to pursue legitimate goal (protection of the population from COVID-19); to be necessary in democratic society. Mandatory vaccination of healthcare professionals against COVID-19 should be used if the goal of protecting the population from COVID-19 cannot be achieved in other ways. Mandatory vaccination of medical personnel against COVID-19 is not the same as forced vaccination. The medical employee chooses whether to be vaccinated against COVID-19 or not according to his own views, values, no matter how irrational, unreasonable, shortsighted they may be in the opinion of the state and other people. The state does not have the right to use forced vaccination, but may apply the following: a range of measures to clarify, persuade, encourage mandatory vaccination of medical personnel against COVID-19, which may be direct or indirect, but not violent; sanctions for refusal from mandatory vaccination of medical personnel from COVID-19 who have no contraindications (suspension from medical activities, fines, etc.). Conclusions. The data obtained in this way allow us to develop further proposals for improving legal regulation of vaccination in Member States of the Council of Europe and increase the effectiveness of ensuring the rights of medical personnel, reduce tensions within society.